Reproducibility of mandibular landmarks for three-dimensional assessment - Corte-Real, Ana (2020)
Mandible can be an elective bone for human identification. This study aimed to test the reproducibility of mandibular landmarks in three-dimensional reconstructions. Cone-beam computed tomography of 17 patients from 7 to 20 years were collected at University of Coimbra database and reconstructed in Mimics Innovation Suite 17.0. Twenty-five landmarks were demarcated for thirty measurements. Reproducibility was evaluated with Intraclass Correlation Coefficient (ICC) for intra-examiner agreement and Technical Error of Measurement (TEM) for interexaminer error, with P < 0.05. Excellent intra-examiner agreements and acceptable inter-examiner errors were found for variables. The reproducibility was confirmed, validating its applicability in forensic purposes.